2013
DOI: 10.1590/s1983-14472013000300023
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidade de adolescentes escolares às DST/HIV, em Imperatriz - Maranhão

Abstract: The aim of this study was to investigate the vulnerability of adolescent students related to sexually transmitted diseases (STD) and the human immunodeficiency virus (HIV), identifying the main risk behaviors and prevention. This quantitative, cross-sectional study was performed in three public schools in Imperatriz--Maranhão, with 295 adolescents, using a structured questionnaire. The results show that: most young people (86.3%) who used a condom the last time they had intercourse, usually keep this practice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
23

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 16 publications
2
13
0
23
Order By: Relevance
“…Currently, despite condoms being one of the most known prevention methods, encouraged by the Brazilian health system, it is possible to notice, especially from a younger audience, a reduction and significant resistance to using them 8,15,20,21 , which corroborates findings in this study. This phenomenon is also known as condom fatigue, and has been observed in other parts of the world 21 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Currently, despite condoms being one of the most known prevention methods, encouraged by the Brazilian health system, it is possible to notice, especially from a younger audience, a reduction and significant resistance to using them 8,15,20,21 , which corroborates findings in this study. This phenomenon is also known as condom fatigue, and has been observed in other parts of the world 21 .…”
Section: Discussionsupporting
confidence: 89%
“…For instance, there is stability and, in some of the most vulnerable groups, increase in the fertility rate of this population, especially in adolescents aged less than 15 years who live in Latin American countries 2 , including Brazil 3 . Additionally, we observe that the young population has a high burden of diseases related to unwanted pregnancies and births, not to mention sexually transmitted infections (STI), including the human immunodeficiency virus / human immunodeficiency syndrome (HIV/ AIDS), maternal death and abortion [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isto se deve à ideia de invulnerabilidade, ao estabelecimento de um relacionamento estável e ao uso de métodos contraceptivos, dentre outros fatores. Apesar da educação, da informação e do saber não pressuporem alteração de atitudes sobre IST/AIDS são facilitadores das mudanças no comportamento sexual reduzindo a susceptibilidade a estas infecções 7 .…”
Section: Conhecimento De Alunas De Uma Universidade Federal Sobre Doeunclassified
“…In recent years, it was observed that sexual initiation has been increasingly early, around 14 to 15 years old, but this decision varies between men and women. 10 It is true that the perception of sexual activity and the love life of adolescents in this generation is quite different from previous generations, due to multiple sexual partners, diversity and form of relationship, providing increased acquisition of infection or pregnancy. 9 With regard to the age of the students, this study can evaluate individuals from 14 years old to students above 20 years old, which according to the studies evaluated they are within the age group referring to the beginning of most of the sexual life individuals nowadays.…”
Section: Sexual Guidance In Schoolmentioning
confidence: 99%